Sinergi Multidisipliner melalui KKN MBKM Desa Tanjung Rambutan: Pemberdayaan Desa, Pendidikan Inklusif, dan Tujuan Pembangunan Berkelanjutan - Fernandes Simamora; Ledy Diana; Beta Floren Hutabarat; Muhammad Hafas Rivaldi; Fikra Ardiansyah; Michelle Cantika Jamalis Putri; Khoirunnisa Nurul Izzati; Syahzia Haiqa Rahman; Meri Meri; Adinda Fareyzi; Intan Habibah Tinara (Lembaga Penelitian dan Pengabdian kepada Masyarakat Universitas Riau, 2025)
Quality, safe, and inclusive education is a fundamental prerequisite for achieving sustainable development. However, bullying at the elementary school level remains a significant barrier to creating an ideal learning environment. This activity aims to implement an anti-bullying socialization innovation based on a multidisciplinary approach at SDN Tanjung Rambutan, integrating legal, psychological, educational, and visual communication perspectives. The methods employed include interactive socialization sessions, group discussions, educational drama, student experience collection through the Kotak Hati Nurani (Heart Conscience Box), and the creation of anti-bullying posters as visual learning media. The results indicate an increased understanding among students regarding the forms and impacts of bullying, greater willingness to report incidents, and the establishment of a safer and more inclusive school culture. These findings demonstrate that a cross-disciplinary approach is effective in fostering early legal awareness and empathy among students. This innovation contributes to the achievement of Sustainable Development Goals (SDG) 4 on quality education and SDG 16 on peace, justice, and strong institutions.